(untitled) (Bangladesh Journal of Urology, 2020)
This prospective double blind comparative study was designed to compare the effect of Dutasteride on the perioperative blood loss in Transurethral Resection of Prostate (TURP).Sixty patients with BPH underwent TURP were divided into 2 groups. Patients belong to the group B (Control) and group A (Experimental). Experimental group patients were given Cap. A (dutasteride 0.5 mg) before two weeks of TURP and group B (control) were given Cap. B (placebo). Postoperative comparison between two groups showed that there were no significant difference between the weight of resected prostatic tissue (control =22.41±6.83 gm, and experimental = 25.38±7.22 gm; p=0.107). Postoperative hemoglobin level of both group (Control group = 10.78±0.64 gm/dL and experimental group = 10.83±.51 gm/dL) revealed no significant difference (p=0.774). The mean hemoglobin loss per gram of prostate tissue in both groups (control = 1.81±0.81 gm/gm and experimental = 1.79±0.88 gm/gm) did not show any statistical difference (p=0.938). In this the study it was found that if the BPH patients are subjected with dutasteride 0.5mg before 2 weeks of TURP, bleeding decrease slightly (Control group = 20.35±7.99 ml/gm and Experimental groups = 17.41±7.70 ml/gm). However, these data of bleeding loss did not show any statistical significance. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.177-181